2019
DOI: 10.1001/jamanetworkopen.2019.5742
|View full text |Cite|
|
Sign up to set email alerts
|

Comparison of Outcomes After Transcatheter Aortic Valve Replacement vs Surgical Aortic Valve Replacement Among Patients With Aortic Stenosis at Low Operative Risk

Abstract: This comparative effectiveness cohort study examines 30-day and 3-year survival among Finnish patients with aortic stenosis at low operative risk who underwent transcatheter aortic valve replacement compared with surgical aortic valve replacement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 36 publications
0
27
0
Order By: Relevance
“…Our initial search yielded 1,827 citations, 58 of which were judged to be potentially eligible and underwent full text review. Ten studies were found to be eligible for inclusion after full text review, four RCTs 8,9,18,19 and six PSM studies [20][21][22][23][24][25] . There were two studies from the OBSERVANT registry 20,23 , of which only the study by Rosato et al 23 intentionally included only low surgical risk patients, while the study by Fraccaro et al 20 was limited to patients older than 80 and intended to include also intermediate-risk patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our initial search yielded 1,827 citations, 58 of which were judged to be potentially eligible and underwent full text review. Ten studies were found to be eligible for inclusion after full text review, four RCTs 8,9,18,19 and six PSM studies [20][21][22][23][24][25] . There were two studies from the OBSERVANT registry 20,23 , of which only the study by Rosato et al 23 intentionally included only low surgical risk patients, while the study by Fraccaro et al 20 was limited to patients older than 80 and intended to include also intermediate-risk patients.…”
Section: Resultsmentioning
confidence: 99%
“…AVA: aortic valve area; AVG: aortic valve gradient; CKD: chronic kidney disease; CVA: cerebrovascular accident; DM: diabetes mellitus; EF: ejection fraction; NA: not available; NYHA: New York Heart Association; PVD: peripheral vascular disease *the patient characteristics are reported for a PSM cohort of 405 matched pairs, the mortality data included in this meta-analysis are derived from 191 matched pairs of patients with STS score <4%. $ definitions of CKD in each study: [8] Creatinine >2 mg/dL, [9] Creatinine >2 mg/dL, [18] Creatinine >200 mmol/L, [19] Creatinine >2 mg/dL, [23] Creatinine >1.2 mg/dL, [24] Creatinine >200 mmol/L, [25] eGFR <30 mL/min/1.73 m 2 .…”
Section: Impact On Daily Practicementioning
confidence: 99%
“…The indications for TAVR are expanding, but it is controversial whether TAVR should be performed on a larger scale because of limited data on the long-term outcome and valve durability of TAVR prostheses compared to SAVR prostheses. Similar longer-term survival after TAVR and SAVR is observed in randomized controlled trials [1,6,7], but studies reporting outcomes in the realworld populations have discordant findings [9][10][11][12]. Sustained valve hemodynamics and low reintervention rate is associated with the use of first-generation balloon-expandable Sapien bioprosthesis [1,13].…”
Section: Introductionmentioning
confidence: 86%
“…11 A retrospective comparative effectiveness cohort study of the Nationwide Finnish Registry revealed no significant difference in mortality outcomes between low-operativerisk patients who underwent TAVR with third generation devices and propensity scoreÀmatched pairs. 12 Lastly, it is possible that the surgeons involved in the treatment centers were simply superior technically and perioperative care was exceptional. The authors also noted the E-AVR registry was designed to look at outcomes among 6 countries (France, Germany, Italy, Spain, Switzerland, and the United Kingdom), but the data cited in this article were only from 3 countries (France, Italy, and Spain) without acknowledgment as to why that was the case.…”
mentioning
confidence: 99%